A novel agile method for user stories’ XMI model generation via NLP and MDA - Kharmoum, Nassim; Retal, Sara; Hajjaj, Mouna; Lagmiri, Souad Najoua; Rhazali, Yassine (Bulletin of Electrical Engineering and Informatics, 2024)
Agile software development methodologies have grown in popularity during the past few years. One of the key components of agile development is the use of user stories to describe software requirements. However, creating and managing user stories can be time-consuming and error-prone. In this paper, we present a novel method to generating user stories’ XMI model using natural language processing (NLP) and model-driven architecture (MDA) approach. We devel-oped a method that uses NLP to extract key information from user stories and then applies MDA techniques to generate an XMI model conforming to its pro-posed meta-model. We conducted a case study to illustrate and validate our method, and we analyze and discuss the studied-related work with our proposal. As a result, our method has the potential to make user stories’ models and their meta-models the focus of software development. This will help to streamline the development process by making it easier to construct and transform models in an agile environment with the MDA approach.